Bursty spike trains of antennal thermo- and bimodal hygro-thermoreceptor neurons encode noxious heat in elaterid beetles. (February 2018) - Nurme, Karin; Merivee, Enno; Must, Anne; Di Giulio, Andrea; Muzzi, Maurizio; Williams, Ingrid; Mänd, Marika
Abstract: The main purpose of this study was to explain the internal fine structure of potential antennal thermo- and hygroreceptive sensilla, their innervation specifics, and responses of the sensory neurons to thermal and humidity stimuli in an elaterid beetle using focused ion beam scanning electron microscopy and electrophysiology, respectively. Several essential, high temperature induced turning points in the locomotion were determined using automated video tracking. Our results showed that the sensilla under study, morphologically, are identical to the dome-shaped sensilla (DSS) of carabids. A cold-hot neuron and two bimodal hygro-thermoreceptor neurons, the moist-hot and dry-hot neuron, innervate them. Above 25–30 °C, all the three neurons, at different threshold temperatures, switch from regular spiking to temperature dependent spike bursting. The percentage of bursty DSS neurons on the antenna increases with temperature increase suggesting that this parameter of the neurons may encode noxious heat in a graded manner. Thus, we show that besides carabid beetles, elaterids are another large group of insects with this ability. The threshold temperature of the beetles for onset of elevated locomotor activity (OELA) was lower by 11.9 °C compared to that of critical thermal maximum (39.4 °C). Total paralysis occurred at 41.8 °C. The threshold temperatures for spike bursting of the sensory neurons in DSS and OELA of the beetles coincide suggesting that probably the spike bursts are responsible for encoding noxious heat when confronted. In behavioural thermoregulation, spike bursting DSS neurons serve as a fast and firm three-fold early warning system for the beetles to avoid overheating and death. Graphical abstract: fx1 Highlights: Inner structure of the antennal dome-shaped sensilla in an elaterid was clarified. They house a cold-hot and two thermo-hygroneurons (moist-hot and dry-hot neuron). All the three neurons were able to encode noxious heat by their bursty spike trains. Threshold temperatures for bursting and elevated mobility of the beetles coincided. Spike burst probably induce escape behaviour in insects to avoid overheating.